Prevalence of blindness and visual impairment and its causes among people aged 50 years and above in Karnali Zone, Nepal - Dulal, S; Sapkota, Y D (Nepalese Journal of Ophthalmology, 2012)
Objective: To estimate the prevalence of blindness and visual impairment and its causes among those aged 50 years and above in Karnali Zone. Materials and methods: Stratified cluster sampling method was used. Twenty four clusters of 50 people aged 50 years and above were selected for the study. Visual acuity was recorded with simplified vision testing card with one optotype “E” of size 60 on one side and size 18 on the other side. Examination by ophthalmologist under mydriasis was done for those with a pinhole visual acuity of less than 6/18. Results: Of 1200 enumerated persons 1,174 were examined (97.8% response rate). The prevalence of blindness (VA <3/60 in better eye) with available correction was 3.4% (40), (95% CI=2.36-4.44); 2.3% (15) for male and 4.8% (25) for female; with best correction it was 1.6% (19), (95% CI=0.9-2.34), 1.1% (7) for male and 2.3% (12) for female. Untreated cataract was the cause of blindness in 67.5%. Severe visual impairment (<6/60 - 3/60 BCVA in better eye) was seen in 2.1% (1.1% male and 3.4% female). Refractive error was the cause of visual impairment in 36.8% and untreated cataract in 58.8%. Conclusion: Cataract and refractive error are the commonest cause of blindness and visual impairment. Females are 3 times more prone to blindness than their male counterpart. Accessible and equitable services are necessary for blindness prevention. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6545 Nepal J Ophthalmol 2012; 4 (2): 282-287